P‐removal for restoration of Nardus grasslands on former agricultural land: cutting traditions. (23rd August 2017) - Schelfhout, Stephanie; Mertens, Jan; Perring, Michael P.; Raman, Maud; Baeten, Lander; Demey, Andreas; Reubens, Bert; Oosterlynck, Simon; Gibson‐Roy, Paul; Verheyen, Kris; De Schrijver, An
Abstract: Past intensive land use complicates the successful restoration of oligotrophic species‐rich grassland types. One of the major bottlenecks are the elevated nutrient levels due to fertilization, especially residual phosphorus (P). Aiming to deplete nutrients, managers often reintroduce traditional haymaking management, sometimes combined with grazing. Here, we evaluate whether this technique restores the abiotic and biotic boundary conditions for restoration of Nardus grassland. Seven grasslands were selected in Flanders, Belgium, which had elevated nutrient levels after the cessation of intensive agriculture 16–24 years ago, and which have been mown and grazed since. We compared soil and vegetation data of these postfertilization grasslands with 34 well‐developed oligotrophic Nardus grasslands. Mowing and grazing did not cause community composition to resemble that of Nardus grassland. Furthermore, bioavailable P‐concentrations were significantly higher in the postfertilization grasslands and P‐limitation was not obtained. Restoring P‐poor soil conditions through continued mowing and grazing management would take at least decades. Phosphorus‐mining can shorten the restoration time by increased P‐removal. Given our results, we propose a decision framework to aid planners and managers in their choice of interventions. Cost‐effective efforts for restoration should be well‐prepared, including measurements of important initial soil characteristics. This allows for an evaluation of "distance to target" and the selection of an effective restoration technique. These techniques may involve cutting the mowing tradition, and utilizing P‐mining or topsoil removal instead.